2020
DOI: 10.11648/j.ijcu.20200402.13
|View full text |Cite
|
Sign up to set email alerts
|

Urological Emergency in a University Hospital Setting: Epidemiological, Diagnostic and Therapeutic Aspects

Abstract: Aim: To report the epidemiological and diagnostic aspects and evaluate the management of urological emergency in a university hospital. Patients and method: We conducted a single-center retrospective descriptive study over the period January 2015 to December 2017. We collected medical records of patients with urological emergency referred by the urology care team in our center. Results: Three hundred patients were identified over a period of 36 months. The mean age of the patients was 47.8±22.9 years (2 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In the study of Bah and Diallo [21] in Guinea, the rate of AUR was reported as 73.9%. In the study of Ndiaye M et al [22], the most common urological emergency was hematuria with a rate of 25.6%. The rate of AUR is seen in the second frequency with 21.6% and it was found to be higher than in our study.…”
Section: Discussionmentioning
confidence: 95%
“…In the study of Bah and Diallo [21] in Guinea, the rate of AUR was reported as 73.9%. In the study of Ndiaye M et al [22], the most common urological emergency was hematuria with a rate of 25.6%. The rate of AUR is seen in the second frequency with 21.6% and it was found to be higher than in our study.…”
Section: Discussionmentioning
confidence: 95%